ANALISIS RASIO CAR, NPL, DAN LDR TERHADAP ROA: Studi Pada Bank Umum Go Public Tahun 2018 – 2020 - Muhammad Taufiqur Rahman; Pompong B Setiadi; Sri Rahayu (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
ABSTRACT Banks are intermediary institutions for those who have excess funds and those who lack funds. The purpose of this study is as follows to test and analyze the ratio of CAR, NPL, and LDR simultaneously affect ROA, the ratio of CAR, NPL and LDR partially affect ROA and between CAR, NPL, and LDR which variable has a dominant influence on ROA. This analysis was carried out with a descriptive qualitative approach, in which the researcher systematically compiled the data obtained based on the results of interviews and group discussions. The conclusion of this study explains that the CAR variable shows a positive and significant effect on ROA. The NPL and LDR variables show a negative and insignificant effect on Return On Asstes (ROA). And the variable with the most dominant influence on ROA is CAR.